2017
DOI: 10.1016/j.jcmgh.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Acinar-to-Ductal Metaplasia Induced by Transforming Growth Factor Beta Facilitates KRAS G12D -driven Pancreatic Tumorigenesis

Abstract: Background & AimsTransforming growth factor beta (TGFβ) acts either as a tumor suppressor or as an oncogene, depending on the cellular context and time of activation. TGFβ activates the canonical SMAD pathway through its interaction with the serine/threonine kinase type I and II heterotetrameric receptors. Previous studies investigating TGFβ-mediated signaling in the pancreas relied either on loss-of-function approaches or on ligand overexpression, and its effects on acinar cells have so far remained elusive.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 76 publications
2
55
0
3
Order By: Relevance
“…They then acquire ductal features through a transdifferentiation process, called acinarto-ductal metaplasia (ADM), leading to premalignant lesions (Grippo et al, 2003). Erosion of the acinar identity, which is promoted by transforming growth factor-b (TGF-b) or a defined set of transcription factors, including PDX1 and SOX9, is necessary to provide a permissive environment for KRAS-driven ADM (Chuvin et al, 2017;Roy and Hebrok, 2015). Injury and stress signaling have also been shown to converge to activate the expression of the OSKM factor KLF4, a pancreatic ductal fate determinant critical for acinar-to-ductal cell reprogramming p53 as a Guardian of the Genome and Epigenome The key role of p53 in mediating cell-cycle arrest or programmed cell death in response to intrinsic stress signals associated with tumorigenesis, including unscheduled DNA replication, telomere erosion, chromosome segregation anomalies, nutrient deprivation, or hypoxia, is generally believed to underlie the frequency of somatic TP53 mutations in human adult carcinomas.…”
Section: Induced Reprogramming Of Differentiated Cells As An Earlymentioning
confidence: 99%
“…They then acquire ductal features through a transdifferentiation process, called acinarto-ductal metaplasia (ADM), leading to premalignant lesions (Grippo et al, 2003). Erosion of the acinar identity, which is promoted by transforming growth factor-b (TGF-b) or a defined set of transcription factors, including PDX1 and SOX9, is necessary to provide a permissive environment for KRAS-driven ADM (Chuvin et al, 2017;Roy and Hebrok, 2015). Injury and stress signaling have also been shown to converge to activate the expression of the OSKM factor KLF4, a pancreatic ductal fate determinant critical for acinar-to-ductal cell reprogramming p53 as a Guardian of the Genome and Epigenome The key role of p53 in mediating cell-cycle arrest or programmed cell death in response to intrinsic stress signals associated with tumorigenesis, including unscheduled DNA replication, telomere erosion, chromosome segregation anomalies, nutrient deprivation, or hypoxia, is generally believed to underlie the frequency of somatic TP53 mutations in human adult carcinomas.…”
Section: Induced Reprogramming Of Differentiated Cells As An Earlymentioning
confidence: 99%
“…To refer to previous literature, [29][30][31][32] pancreatic islet tissue damaged was extracted, and paraffin sections preconditioning dewaxed to water, 40 g/L paraformaldehyde fixed for 15 minutes and PBS washed for 5 minutes ×2 times, 20 mg/L protease K solutions dissolved in Tris/HCL (pH 7.4-8.0) for 20 minutes at 37°C, then PBS washed for 5 minutes ×3 times and added 50 µL TUNEL reaction liquid at 37°C for 60 minutes, PBS washed for 5 minutes ×3 times and added 50 µL POD at 37°C for 30 minutes, DAB colored for 5-10 minutes and PBS washed for 5 minutes ×3 times, and hematoxylin counterstain for 1 minute. Then the slices were washed, dehydrated transparent, sealed and observed; TUNEL reaction were replaced via PBS and was acted as negative control.…”
Section: Apoptosis Evaluationmentioning
confidence: 99%
“…Besides, the pharmacological inhibition of HSF1 suppressed the formation of ADM and PanINs (in other words, HSF1 inhibition may suppress pancreatic cancer initiation in KC mice). Notably, for normal pancreatic acinar cells, plasticity is an important feature, which means that these cells can recover from ADM to assume normal acinar functions when the self/external pressure (such as pancreatitis and pancreas injury) are removed [34]; however, in the context of Kras oncogene mutation, regardless of whether there is a stimulus present or not, the fate of pancreatic acinar cells is set (irreversible ADM, subsequent PanINs and ultimately PDAC) [35]. Similarly, we found that only acinar edema remained in vehicle C mice pancreases when they recovered from pancreatitis; however, vehicle KC mice pancreases exhibited a large amount of pancreatitis-induced ADM, PanINs and even PDAC (along with an abundant desmoplastic reaction).…”
Section: Discussionmentioning
confidence: 99%